2001
DOI: 10.1148/radiology.219.2.r01ma03527
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging-guided Stent Placement in Iliac Arterial Stenoses: A Feasibility Study

Abstract: MR imaging-guided stent placement in iliac arteries is feasible in select patients. The presented technique has limitations-that is, long procedure times, lack of real-time monitoring, and stent artifacts-that necessitate further modifications before it can be recommended for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 31 publications
0
53
0
2
Order By: Relevance
“…10,11 To our knowledge, the current report represents the first MR-guided coronary artery stent placement. Improved gradient performance, ultrafast reconstruction capabilities, 14 and recently developed software tools for "on-the-fly" interactive MR scanning 18 now offer the potential for real-time MR imaging with sufficient contrast and spatial resolution for MR-guided coronary interventions.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…10,11 To our knowledge, the current report represents the first MR-guided coronary artery stent placement. Improved gradient performance, ultrafast reconstruction capabilities, 14 and recently developed software tools for "on-the-fly" interactive MR scanning 18 now offer the potential for real-time MR imaging with sufficient contrast and spatial resolution for MR-guided coronary interventions.…”
Section: Discussionmentioning
confidence: 88%
“…4 The combination of MR plaque information with interventional MR-guided coronary stent placement may provide a favorable clinical potential. In contrast to MR-guided stent placement in peripheral arteries, 10,11 coronary MR-guided interventions must accommodate the substantial motion artifacts originating from the respiratory and the cardiac cycles. 12 In addition, MR-guided coronary artery interventions are especially challenging because of the small size and the tortuous anatomy of the coronary vessels.…”
mentioning
confidence: 99%
“…Advances in rapid imaging, combined with development of catheter devices visible under MRI, have made real-time MRI (rtMRI)-guided therapeutic interventions feasible. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] We hypothesize that rtMRI can guide catheter navigation within an occluded artery and that combined CTO recanalization and percutaneous transluminal angioplasty can be conducted en-tirely under rtMRI guidance with the use of custom MRIvisible devices in a swine model.…”
Section: Editorial P 1053 Clinical Perspective P 1107mentioning
confidence: 99%
“…MR HAS BEEN PROPOSED as an imaging modality to guide endovascular therapies (1)(2)(3)(4)(5)(6). Recent developments, demonstrated in animals, include positioning of catheters into the carotid arteries (2), the renal artery (4,5), and the iliac artery (3), and coil placement in experimental aneurysm models (6).…”
mentioning
confidence: 99%
“…Recent developments, demonstrated in animals, include positioning of catheters into the carotid arteries (2), the renal artery (4,5), and the iliac artery (3), and coil placement in experimental aneurysm models (6). In an editorial, Strother (1) suggested that the real advantage of MRguided endovascular therapies may not be to improve catheter guidance, but rather to provide added value by improving the monitoring of therapy.…”
mentioning
confidence: 99%